Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/plants10040696
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Morpho-Physiological, Biochemical and Antioxidant Responses of Tomato Landraces to Salinity Stress

Abstract: Understanding salt tolerance in tomato (Solanum lycopersicum L.) landraces will facilitate their use in genetic improvement. The study assessed the morpho-physiological variability of Hail tomato landraces in response to different salinity levels at seedling stages and recommended a tomato salt-tolerant landrace for future breeding programs. Three tomato landraces, Hail 548, Hail 747, and Hail 1072 were tested under three salinity levels: 75, 150, and 300 mM NaCl. Salinity stress reduced shoots’ fresh and dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 81 publications
(88 reference statements)
2
13
0
Order By: Relevance
“…Our results showed that the tomato plants that were exposed to salt stress had significantly decreased shoot length and fresh weight compared to the control plants. These results agreed with those obtained by Alzahib et al (2021) [ 15 ], in which a high concentration of NaCl (0.3 M) decreased tomato plant growth, leaf area, plant height, and fresh and dry root weights.…”
Section: Resultssupporting
confidence: 93%
“…Our results showed that the tomato plants that were exposed to salt stress had significantly decreased shoot length and fresh weight compared to the control plants. These results agreed with those obtained by Alzahib et al (2021) [ 15 ], in which a high concentration of NaCl (0.3 M) decreased tomato plant growth, leaf area, plant height, and fresh and dry root weights.…”
Section: Resultssupporting
confidence: 93%
“…Excessive Na + ions participate in ROS production by working as signaling molecules in transduction pathways ( Fatima et al, 2021 ). The excessive accumulation of Na + denatures the enzyme needed to synthesize chlorophyll and therefore reduces the synthesis of chlorophyll ( Alzahib et al, 2021 ). However, PM alleviated this reduction, which indicates PM application reduced the excessive Na + accumulation, which protects photosynthetic apparatus from damaging effects of Na + and reduces the activities of chlorophyll degrading enzymes, improving chlorophyll synthesis under salinity stress ( Sheoran et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the generation and transport of biomass is also an important factor in assessing the degree of salt stress in plants 26 . Studies have shown that salt stress reduces plant biomass synthesis, and that plant leaves are capable of responding to salt stress via the rapid accumulation of proline 27 29 . In our experiment, under the stress condition of low salt B (200 mM NaCl), the fresh weight and root/shoot ratio of R. soongorica seedlings increased, and low salt had a significant promotional effect on their growth.…”
Section: Discussionmentioning
confidence: 99%